Materiality and Discursivity of Cyber Violence Against Women in India. (March 2023) - Sarkar, Sahana; Rajan, Benson
With the advent of the digital age and online networks, a new facet of human experience materialised called the cyberspace. In other words, it is an addition to an individual's intrapsychic world. Millions of people are using the Internet as a day-to-day activity to enhance their lives while at the same time there are people who are using it for anti-social purposes such as stalking, harassing, bullying and so on. This, with the advent of the Internet, has become a new weapon of abuse. This research intends to bring the two realms of virtual and physical, which are considered as binaries into a productive dialogue on violence against women. In doing so, it takes forward the narratives of cyber violence survivors into rethinking the construction of disembodied and embodied violence. I pursue this aim by exploring how women survivors of India conceptualise and respond to cyber violence. This is a qualitative exploratory study located within the theoretical framework of feminist standpoint theory in order to engage each survivor's story from their individual standpoint. An in-depth interview was conducted for 30 women survivors in India. This study will help to critically understand cyber violence as an embodied experience.